Early Atherosclerosis in HIV Infected Subjects on Suppressive Antiretroviral Treatment: Role of Osteoprotegerin. (5th December 2013) - D'Abramo, Alessandra; D'Agostino, Claudia; Oliva, Alessandra; Iannetta, Marco; D'Ettorre, Gabriella; Vullo, Francesco; Mancone, Massimo; Ciardi, Maria Rosa; Mastroianni, Claudio Maria; Vullo, Vincenzo
Abstract : Cardiovascular disease is increased in HIV-infected patients. Cytokines such as osteoprotegerin are implicated in atherosclerosis. The aim of our study was to evaluate the role of osteoprotegerin in the development and progression of atherosclerosis in HIV infected subjects on suppressive antiretroviral treatment. We enrolled 76 patients; 35 HIV infected men on suppressive Highly Active Antiretroviral Therapy with Framingham score <10%; 21 HIV negative individuals matched for age, gender, and Framingham score, and 20 subjects with Framingham score >10% as control groups. HIV positive subjects underwent echocardiography, electrocardiography, and heart multidetector computed tomography, whereas in HIV negative subjects, tomography was only performed in case of any abnormalities either in echocardiography or electrocardiography. In HIV positive patients, computed tomography showed stenosis in 51.4% of the subjects. Osteoprotegerin plasma levels were higher in HIV-infected patients than those in healthy controls but lower than in HIV negative subjects with Framingham score >10%. Higher osteoprotegerin plasma levels were found in HIV positive patients with grade I stenosis than in patients with grade II/III stenosis. In conclusion, in HIV infected subjects with Framingham score <10%, osteoprotegerin plasma concentrations are associated with atherosclerosis, in particular at the early stage of the process.